2022
DOI: 10.3390/jpm12071030
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Biological Network Analysis and Drug Repurposing Based on Leukocyte Transcriptomics in Severe COVID-19: In Silico Systems Biology to Precision Medicine

Abstract: The coronavirus disease 2019 (COVID-19) pandemic causes many morbidity and mortality cases. Despite several developed vaccines and antiviral therapies, some patients experience severe conditions that need intensive care units (ICU); therefore, precision medicine is necessary to predict and treat these patients using novel biomarkers and targeted drugs. In this study, we proposed a multi-level biological network analysis framework to identify key genes via protein–protein interaction (PPI) network analysis as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 153 publications
(182 reference statements)
2
10
0
Order By: Relevance
“…Additionally, these DEGs were mainly enriched in cellular senescence, complement and coagulation cascades, organelle fission, DNA replication, and P53 signaling pathways. Sagulkoo illustrated that upregulated DEGs in COVID-19 were mainly concentrated on cell division, cell cycle, and innate immune signaling pathways, which was consistent with our study (Sagulkoo et al 2022 ). Lucy Kundura discovered that the monocyte of COVID-19 can spontaneously release ROS (reactive oxygen species, ROS) which was able to result in DNA damage and apoptosis in neighboring cells.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, these DEGs were mainly enriched in cellular senescence, complement and coagulation cascades, organelle fission, DNA replication, and P53 signaling pathways. Sagulkoo illustrated that upregulated DEGs in COVID-19 were mainly concentrated on cell division, cell cycle, and innate immune signaling pathways, which was consistent with our study (Sagulkoo et al 2022 ). Lucy Kundura discovered that the monocyte of COVID-19 can spontaneously release ROS (reactive oxygen species, ROS) which was able to result in DNA damage and apoptosis in neighboring cells.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, these DEGs were mainly enriched in cellular senescence, complement and coagulation cascades, organelle ssion, DNA replication, and P53 signaling pathways. Pakorn Sagulkoo illustrated that upregulated DEGs in COVID-19 were mainly concentrated in cell division, cell cycle, and innate immune signaling pathways, which was consistent with our study 21 . Lucy Kundura discovered that the monocyte of COVID-19 spontaneously released ROS (reactive oxygen species, ROS) able to result in DNA damage and apoptosis in neighboring cells.…”
Section: Discussionsupporting
confidence: 91%
“…We also found the basis for the association of hsa-mir-124-3p and hsa-let-7b-5p with the developmental process of COVID-19. [48,49] We performed genes-diseases analysis to predict the association between hub genes and related diseases, and we found 284 diseases with significant association with hub genes, and we screened the top 20 diseases as the most significantly associated with hub genes. We constructed genes-diseases networks and found that such as liver carcinoma of cortical development was significantly associated with hub genes.…”
Section: Discussionmentioning
confidence: 99%
“…We also found the basis for the association of hsa-mir-124-3p and hsa-let-7b-5p with the developmental process of COVID-19. [ 48 , 49 ]…”
Section: Discussionmentioning
confidence: 99%